The Relationship Between Postpartum Mothers' Knowledge of Breast Care and Smooth Breastmilk Production (International Forum of Researchers and Lecturers, 2025)
Breast care is a critical aspect of ensuring optimal breastmilk production during both the prenatal and postnatal periods. Adequate knowledge and proper practices related to breast care play a vital role in supporting successful breastfeeding, which directly contributes to infant nutrition and maternal health. This study aimed to determine the association between postpartum mothers' understanding of breast care and the effectiveness of breastmilk production at Labuang Baji Regional Hospital in Makassar in 2021. An analytical observational method with a cross-sectional design was utilized. The sample consisted of 32 postpartum mothers, selected through total sampling. Data collection involved assessing mothers’ knowledge levels and evaluating the smoothness of their breastfeeding experience. The analysis was conducted using the Chi-square statistical test. Findings revealed that among the 32 participants, 15 mothers (46.9%) who had a good understanding of breast care experienced smooth milk flow, whereas 3 mothers (9.4%) with good knowledge still reported non-smooth lactation. Conversely, 5 respondents (15.6%) with poor knowledge still managed smooth breastfeeding, and 14 mothers (43.8%) with poor knowledge faced challenges with milk production. The Chi-square test indicated a statistically significant association between knowledge of breast care and breastmilk flow (p = 0.006), suggesting that knowledge levels strongly influence breastfeeding outcomes. These results highlight the importance of targeted education for postpartum mothers on proper breast care techniques. It is recommended that healthcare providers increase efforts in promoting breast care awareness as part of postnatal care services to support improved breastfeeding practices and enhance maternal and infant health outcomes overall.